From Critique to Insight: Student Voices on English Writing Feedback - Wahyudi, Agus; Sari, Farnia; Amaliah; Pamuji, Arief; Yanu Dharmawan, Yanuarius (Universitas Hamzanwadi, 2024)
This study delves into the pivotal role of feedback in English writing instruction, a crucial element for enhancing language proficiency and writing skills among English language learners. The primary aim of the research is to examine students' perceptions of teacher feedback and to identify the types of feedback they receive, which are essential for improving teaching strategies and student outcomes. Utilizing a qualitative methodology, the research analyzed responses from 22 students, collected through a questionnaire adapted from the frameworks of Lee (2011) and Ellis & Sheen (2011) to reflect the local educational setting. The results reveal a mixed reception to teacher feedback: while it is valued for improving writing skills, it also sometimes causes confusion and anxiety due to unclear instructions or the use of complex metalinguistic symbols. The types of feedback reported include direct, indirect, and metalinguistic feedback. Direct feedback proved effective in enhancing clarity and understanding, whereas indirect and metalinguistic feedback was occasionally linked to negative emotions such as anxiety and embarrassment. Despite these challenges, the study concludes that properly structured feedback can significantly foster cognitive development, prompting students to refine their thought processes, explore ideas independently, and become adept at self-correction. This underscores the need for educators to consider both the content and delivery of feedback to maximize its effectiveness and minimize potential stressors for learners.